O PROCESSO PEDAG?GICO E A FORMA??O DO IMIGRANTE ALEM?O NAS COL?NIAS DE BOM JARDIM DO SUL E WITMARSUM (PARAN?). - Eidam, Rodrigo (2009)
This dissertation studies the relationship between the educational process of conscience formation history and negotiation of identity among German immigrants living in S?o Paulo, through the case of two colonies in the region of Campos Gerais (Paran?). The first settlement is Good Garden, founded in the 1920s, who owned a private school in the whole process of teaching and learning was focused on continuity of the ideal German second reading of the leaders of the colony, which included a racial and cultural superiority German. With New State this school came to be closed, its employees harassed and arrested many of them. With the closing of the school and the end of the Vargas regime, this group was to do away this colony and now a German archaic speech, and the new younger generations do not master any language, and has little interest in German identity. The second colony studied, Witmarsum, was established in Santa Catarina and Parana transferred to in 1951. Unlike Bom Jardim, passed without major problems by the Vargas dictatorship, and one of the factors that resulted predominantly for this was equivocal identification of the group as the representatives of German government in order to dominate their own dialect, a mixture German, Dutch and Russian. With the fall of the Estado Novo, the school returned the colony to teach German, leaving in their curriculum and the modern German formal (school is supervised by the community, with teachers in the public state). The research methodology was held on interviews with old settlers in search of his memories of relationships and formal educational non-formal school and non school simulation analysis of personal moral choices on a fictional narrative, and study of documents, mainly photos and materials. Results show that the educational process, different in each colony, was a significant factor in the management of identity in light of new contexts, or not favoring ties of continuity between the original national identity and national identity resulting contemporary of both colonies studied. The reluctance to integrate with the national and strict maintenance of an educational perspective that the German identity conflicted with the local identity (the "shifting cultivators") led the community of Bom Jardim confrontations that resulted in the collapse of the German identity among its participants over time. On the other hand, increased openness and ability to negotiate identity and its reproduction through education in a different historical context, was one of the factors that enabled the colony Witmarsum continued recovery from his perspective of the German identity to this day.